Determination of anion cation balance in dairy cattle herds of Lima and Trujillo, Peru and its relationship with urinary pH - Guzmán, Ángel (2017)
The aim of the present study was to determine the Dietary Cation-Anion Difference (DCAD) concentration in pre-partum diets from nine dairy farms of Lima and Trujillo, Peru. Feed and forage samples were analysed for sodium, potassium, chloride and sulphur in order to calculate DCAD values by mathematical formula. Similarly, urine samples were collected from 76 cows during the pre-partum period to evaluate the relationship between urinary pH and DCAD. The mean DCAD value was 6.62 ± 2.99 mEq/100 g DM for diets of dairy farms in Lima and 13.09 ± 5.36 mEq/100 g DM for diets of dairy farms in Trujillo. Urine pH mean was 7.7, ranging from 6.0 to 8.48. The correlation between DCAD and urine pH values was 0.331.